PENOLAKAN DISPENSASI KAWIN ANAK DI BAWAH UMUR (Studi Penetapan Pengadilan Agama Manna Nomor 0024/Pdt.P/2018/PA.Mna) - Zulvayana, Zulvayana (UIN Fatmawati Sukarno Bengkulu, 2018)
This study aims to determine the legal considerations in rejecting the application of marriage dispensation in the Manna Religion Court and to find out the determination of the Manna Religion Court Number 0024 / Pdt.P / 2018 / PA.Mna in accordance with the elements of legal justice, legal certainty and legal benefits. Based on the results of the research, it is known that the legal consideration of the refusal of marriage dispensation applications because the Petitioners in the trial only submitted 1 (one) witness so that the applicants could not prove the argument of their petition and in court found a fact that the children of the applicant had been married before the application for marriage dispensation was tried . The cause of rejec- tion of marital dispensation of minors due to actions that are contrary to Article 7 of Act Number 1 of 1974. Determination of the Manna Religion Court Number 0024 / Pdt.P / 2018 / PA.Mna is in accordance with the elements of justice, certainty and legal benefit because in the Determination of the application for marriage dispensation is guided by Law Number 1 of 1974. The results of this study, are expected to be a deterrent effect for the community and the Office of Religious Affairs, so as not to violate Law Number 1 Year 1974 by marrying minors without the Religion Court dispensation. The rejection of the granting of marriage dispensation in substantial justice will be difficult to be felt by the applicants, but in order to enforce procedural justice, the stipulation of marital dispensation creates order in recording marriage